Botanical extracts: bioactivity against Spodoptera frugiperda (Lepidoptera: Noctuidae), metabolomic characterization and compatibility with biological control agents - Santana, Emile Dayara Rabelo (2025)
Sustainable agricultural pest management involves the development of insecticides that are effective against target pests and selective for natural enemies. Spodoptera frugiperda is a globally distributed pest that is difficult to control due to cases of resistance to insecticides and Bt technology, which justifies the search for new management strategies. In this context, botanical insecticides represent a promising alternative, especially when combined with biological control using predators and parasitoids. Thus, in the first chapter of this thesis, the insecticidal potential of botanical extracts from species of the Annonaceae and Solanaceae families against S. frugiperda larvae was investigated. Initial toxicity assessments were performed using diets contaminated with crude extract, followed by bioguided fractionation and chemical characterization of the active fractions through metabolomics. Among the extracts tested, the crude leaf extract of Annona montana demonstrated significant bioactivity, leading to further bioguided fractionation. The methanolic fraction (AM-M) exhibited 80.1% larval mortality and weight reduction, while the ethyl acetate subfraction (AM-M2) also showed significant activity. Chemical characterization identified 16 acetogenins, including tucupentol, gigantetronenin, montanacins, and rolliniastatins. In the subsequent chapters, the selectivity of the methanolic fraction AM-M (denoted EFAMON) and other botanical and synthetic insecticides on natural enemies Doru luteipes and Trichogramma atopovirilia were investigated. For D. luteipes, botanical insecticides, including EFAMON, exhibited low toxicity (<30% mortality), while the synthetic insecticide Premio® caused high mortality in nymphs (>80%) and compromised behavioral and reproductive parameters. Regarding T. atopovirilia, the seed extract of A. mucosa (ESAM), as well as the commercial products Anosom® (acetogenin annonin) and Azamax® (azadirachtin + 3-tigloylazadirachtol), significantly reduced parasitism in the F0 generation, while EFAMON and the synthetic insecticide had a lower impact. No transgenerational impacts (F1 and F2). were observed. Overall, the results demonstrate the insecticidal potential of A. montana, particularly due to the acetogenins, and emphasize the selectivity of the methanolic fraction toward natural enemies. These findings support the use of botanical insecticides alongside biological control within integrated pest management (IPM) programs.